Michael Northcott, A Political Theology of Climate Change - Zenner Peppard, Christiana (Journal for the Study of Religion, Nature and Culture, 2018)
Michael Northcott, A Political Theology of Climate Change (Grand Rapids: Eerdmans, 2013), 316 pp., 30.00 (pbk), ISBN: 978-0-8028-7098-8.